Perception of monetary and non-monetary effects on the energy transition: Results of a mixed method approach - Uta Burghard; Barbara Breitschopf; Katharina Wohlfarth; Fabian Müller; Julia Keil (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2021)
When paving the way for steps towards the energy transition, aspects of acceptance and perception of society are relevant and partially crucial to be considered for a successful development. In order to help designing elements that are supported by society, this paper considers monetary and non-monetary effects, from society's perspective, on the energy transition. Starting from a literature review, relevant impacts on micro (effects affecting individuals directly), meso (effects that occur at the energy system level) and macro (effects that individuals consider important for society) levels were differentiated. With these findings in mind, a broad quantitative survey with a sample of 300 participants, as well as online workshops with 55 participants, were conducted to investigate perception and judgement of participation in the energy transition. Whether individuals actively participated or not was differentiated in the analysis. The survey revealed that the dynamics of the energy transition, the environmental effects and the increasing energy costs in financial terms and additional burdens were issues for all participants, while environmental and financial aspects were addressed more often by non-participating individuals. In parallel, workshops were held to identify perceived effects of the energy transition in an open format. Most participants had a generally positive attitude towards the energy transition or its impacts, while the majority also saw increasing burdens for society. Compared to non-participating individuals, the participating individuals were more critical of the implementation of the energy transition and of economical role players in the process. Renewable energies are seen as an important element, with active participation advocated predominantly by the participating group. Concerning personal impacts, participating individuals mostly voiced political views and were concerned that the transition was not happening fast enough. The non-participating individuals focused more on negative effects or failures of the energy transition e.g., higher energy prices or more regulations. Nevertheless, there was overall agreement on the necessity of the energy transition. This study showed once again that participation can increase acceptance of the energy transition. Additionally, access to information can increase the willingness of individuals to participate. Further study of personal values could assist in identifying preferences that affect individual responses to the energy transition. Such information could be used to guide design decisions around future energy transition activities.
urn:nbn:de:0011-n-6410652
Keywords: 330